Hepatitis C: Knowledge and awareness of private dental practitioners of a tricity in India - Ramandeep Singh Gambhir; Mandeep Kumar; Gurminder Singh; Arshdeep Singh; Amanpreet Kaur (Wolters Kluwer Medknow Publications, 2018)
Background: Dental health-care personnel are at an increased risk toward infections caused by various microorganisms including hepatitis B and hepatitis C viruses (HCV). A dentist can play an important role in the prevention of HCV by considering every patient as a potential carrier for hepatitis. Therefore, the present study was conducted to assess the knowledge and awareness of dental health-care professionals regarding various aspects of HCV. Materials and Methods: A cross-sectional study was conducted among 247 private dental practitioners of tricity. A close-ended self-structured questionnaire was administered which contained 12 questions on knowledge and awareness regarding HCV infection keeping in view the time constraints. Categorization of knowledge scores was done at three levels - poor, moderate, and good. Statistical analysis was done using ANOVA and Student's t-test. Results: Nearly 96% (102) of postgraduates and 84% (117) of graduates had heard about HCV. 45.5% (112) had poor knowledge scores, 33.6% (83) had moderate knowledge scores, and only 21% (52) of participants had good knowledge scores. On the opinion of treating an HCV-infected patient by a dentist, only 61% (65) of postgraduates and 46% (64) of graduates agreed. There was statistically significant association of mean knowledge scores with gender, education level, and experience (P < 0.05). Conclusion: Majority of the dental professionals lacked knowledge regarding HCV infection and were not fully aware regarding certain aspects. Therefore, there is an urgent need for modification of the existing dental curriculum so that knowledge regarding these diseases can be imparted during graduation.